The Relationship Between Pharmacist Workload and the Clinical Pharmacy Services Quality of Kulon Progo Regency - Dewi, Dina Nurlita; Annisaa', Eva; Dianingati, Ragil Setia (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice), 2025)
Background: Clinical pharmacy service activities are the decisive roles of pharmacists in ensuring patient safety and quality of life, so there is a need for quality control in their implementation. However, several studies classify the clinical pharmacy services quality at primary health centers as needing improvement. On the other hand, pharmacists at primary health centers in Kulon Progo are overburdened, exceeding the standard rasio.Objectives: This study aims to determine the relationship between the pharmacists workload and the clinical pharmacy services quality.Methods: This study is an analytic observational study with a retrospective and prospective approach. The research participants are five pharmacists from the three sample primary health centers. The pharmacist's workload was measured using the daily log workload form, while the clinical pharmacy services quality was measured using ten indicators of clinical pharmacy service quality. The pharmacist workload is classified into heavy (>80%), moderate (60-80%), or light (<60%) categories. Meanwhile, the quality of clinical pharmacy services is classified into proper (>75%), fair (56-75%), or poor (<56%). The relationship between pharmacist workload and clinical pharmacy service quality was analyzed using the Somers correlation test.Results: The pharmacists’ workload at Sentolo I, Temon I, and Galur II primary health centers, respectively, is heavy (94.05%), heavy (84.55%), and moderate (79.91%). The clinical pharmacy services quality at Sentolo I, Temon I, and Galur II primary health centers, respectively, were fair (56.57%), fair (69.21%), and proper (79.05%). Somers test results show a significant relationship (p=0.014) between the pharmacists’ workload and the clinical pharmacy services quality. The correlation coefficient obtained is -1,000.Conclusion: There is a significant relationship between pharmacist workload and clinical pharmacy service quality.